The Effect of Reviewers’ Self-Disclosure of Personal Review Record on Consumer Purchase Decisions: An ERPs Investigation - Liu, Jianhua; Mo, Zan; Fu, Huijian; Wei, Wei; Song, Lijuan; Luo, Kewen (Frontiers in Psychology, 2021)
The disclosure of reviewers’ personal information on electronic commerce websites has been found to substantially impact consumers’ perceptions regarding the credibility of online reviews. The current study investigated whether the disclosure of personal review record influenced consumers’ information processing and decision making by adopting event-related potentials (ERPs) measures, as ERPs allow for a nuanced examination of the neural mechanisms that underlie cognitive processes. At the behavioral level, we found that the purchase rate was higher and that the reaction time was shorter when the review record was disclosed (vs. when it was not), indicating that the disclosed condition was more favorable to the participants. Moreover, ERPs data showed that the disclosed condition induced an attenuated N400 component and an increased LPP component relative to the undisclosed condition, suggesting that the former condition gave rise to less cognitive and emotional conflict and to more positive evaluations. Thus, by elucidating potential cognitive and neural underpinnings, this study demonstrates the positive impact of reviewers’ disclosure of personal review record on consumers’ purchase decisions.